Analisis Perbandingan Tingkat Kesehatan Bank dengan Menggunakan Pendekatan RGEC (Studi pada PT. Bank Mandiri (Persero), Tbk dan PT. Bank Negara Indonesia (Persero), Tbk Periode 2014-2018) - Marissa Putriana; Susi Artati (Universitas Batanghari, 2019)
This research aims to analyse how the health level comparison of PT Bank Mandiri (Persero), Tbk with PT Bank Negara Indonesia (Persero), Tbk using RGEC (Risk Profile, Good Corporate Governance, Earnings, Capital) approach In 2014-2018. The type of research used is quantitative descriptive research. Research results show the health level of Bank Mandiri and BNI in 2014-2018 overall healthy. Risk Profile Bank Mandiri and BNI bank with the credit risk indicator gained a healthy predicate and with the risk indicators of the liquidity of both banks earned a fairly healthy predicate. Assessment of Good Corporate Governance (GCG) based on Self Assessment showed that Bank Mandiri obtained very good predicate while BNI Bank obtained good predicate. The Earnings assessment of the ROA and NIM ratio analysis and Capital valuation based on the CAR value analysis showed that Bank Mandiri and BNI Bank gained a very healthy predicate.